2011
DOI: 10.1176/appi.ajp.2011.11010048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Shifts During the Decade Following First Admission for Psychosis

Abstract: OBJECTIVE Diagnostic shifts have been prospectively examined in the short-term, but the long-term stability of initial and follow-up diagnoses have rarely been evaluated. METHOD A cohort of 470 first-admission patients with psychotic disorders was systematically assessed at baseline, 6-month, 2-year, and 10-year follow-up. Longitudinal best-estimate consensus diagnoses were formulated after each assessment. RESULTS At baseline, the diagnostic distribution was: schizophrenia spectrum disorders 29.6%, bipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
188
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 239 publications
(209 citation statements)
references
References 38 publications
12
188
1
8
Order By: Relevance
“…Trials were excluded if: -the samples included people with diagnoses of a first psychotic episode since one episode is not necessarily indicative of a full schizophrenia diagnosis, and this population corresponds to younger people with other needs associated with recent interruption of work and educational trajectories [19,20], -the intervention duration was shorter than six months, -no inference test was reported or insufficient descriptive information was provided (percentages or means and variability measures for both groups).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Trials were excluded if: -the samples included people with diagnoses of a first psychotic episode since one episode is not necessarily indicative of a full schizophrenia diagnosis, and this population corresponds to younger people with other needs associated with recent interruption of work and educational trajectories [19,20], -the intervention duration was shorter than six months, -no inference test was reported or insufficient descriptive information was provided (percentages or means and variability measures for both groups).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Even when rigorous approaches are used to establish diagnoses, there may be shifts in the patient's diagnosis over time (Bromet et al 2011;Mueller et al 1999). Thus, the reported presence of a specific diagnosis in the past does not mean that the same diagnosis is accurate or persists.…”
Section: Apa Practice Guidelinesmentioning
confidence: 99%
“…Similarly, long-term studies of mood disorders have described substantial changes in diagnosis from major depressive disorder to bipolar disorder and schizophrenia 18 . A recent study which investigated psychiatric patients at four time points found that only 50% of patients retained their initial diagnosis 19 . Schizophrenia patients had the most stable diagnosis as 78% retained their initial diagnosis.…”
Section: Current Difficulties In Psychiatric Diagnosismentioning
confidence: 99%